The ineffable luminosity of madness in “The Imitation of the Rose” - Junqueira, Luan Felipe de Souza; Scorsolini-Comin, Fabio (Estudos Avançados, 2023)
Guided by Winnicott’s psychoanalysis, the aim of this study is to reflect on the process of psychic illness in the “The Imitation of the Rose”, a short story by Clarice Lispector. Laura, after a period of psychiatric hospitalization, experiences a fragile integration, requiring external elements and figures to provide her with a sense of unity and identity. It is noticed, at all times, the character’s attempt to control her behavior and thoughts, demonstrating that she was fine and would no longer get sick. This story, therefore, allows us to reflect that her psychic illness continues to tailor the character’s relationships even after her period of hospitalization, in an attempt to exert control that, from the start, already revealed her emotional breakdown.